Literature Review: Pengaruh Tingkat Pendidikan,Kemampuan Dan Kompetensi Terhadap Kinerja Guru - Furqon, Muhammad Dzaki; Ali, Hapzi (Peneliti.net, 2025)
In Influence of Education Level and Ability on Teacher Competence and Performance is a literature study of Research that is within the scope of HR research. This article aims to form a hypothesis based on the influence between variables used in future research on the Influence of Education Level and Ability on Teacher Competence and Performance. Google Scholar, Mendeley, and other academic media online libraries can be used to search for research topics. The research method used in the library institution comes from e-books and e-journals that are open to the public. Qualitative analysis based on description. The results of this article: 1) Education Level affects Teacher Performance; 2) Ability affects Teacher Performance; and 3) Competence affects Teacher Performance.